KAJI EKSPERIMEN DAN SIMULASI PENGARUH SUDUT DOUBLE SEGMENTAL BAFFLE DAN LAJU ALIRAN FLUIDA PADA HEAT EXCHANGER JENIS SHELL AND TUBE PADA MESIN MAIN EXTRUDER TERHADAP KEBAIKAN PERPINDAHAN PANAS - Safi'i, Muhamad; Suheri Kertosenjoyo2, Suheri; Nugroho, Agung; Susanto, Susanto; Farhan Putra Arya, M. Iqbal; Heriyani, Oktarina; Effendi, Yafid (Fakultas Teknik dan Ilmu Komputer (FASTIKOM) UNSIQ, 2024)
Shell and Tube Heat Exchanger (STHX) is very important for its use in the industrial world which can support the continuity and success of the entire network process. Various kinds of research have been carried out to increase the heat transfer coefficient and effectiveness of Shell and Tube Heat Exchangers (STHX) both experimentally and by simulation. This research examines the increase in heat change coefficient and effectiveness of STHX with variations in baffle angles of 0°, 10°, and 20° with fluid mass flow rates of 2, 4, and 6 kg/s. As a result, STHX with a baffle angle of 0° has the largest heat change coefficient value than STHX with a baffle angle of 10° and 20° both during experiment and simulation, values ​​ranging from 4218 W/m²C and 4226 W/m²C at a baffle angle of 0° when the fluid flow rate is increased to 6 kg/s. Keywords: Shell and Tube Heat Exchanger, baffle angle configuration, double segmental baffle, total heat transfer coefficient, effectiveness, CFD (Computational Fluid Dynamics).